Cold Chain Maintenance and Vaccine Administration Practices in Hospitals & Clinics of Mangalore City - A Health System's Research - Harsha Kumar HN; Aakanksha Aggarwal (Medsci Publications, 2013)
Background: Problems related to cold chain functioning & vaccine handling have been reported from developed & developing countries. Such studies help programme officers & policy makers. So this study was undertaken. Objectives: The study was conducted with an objective to know the Cold Chain Maintenance & vaccine administration practices in government, private hospitals & clinics of Mangalore city. Material & Methods: This health systems research was conducted in Mangalore City. List of government, private hospitals & private clinics were obtained from District Health Office and Indian Medical Association local chapter. A Pre-Tested semi-structured proforma was used to collect information to meet the objective. After obtaining consent from necessary authorities, these hospitals were visited and observations noted directly in the proforma. Photos were taken if permitted in the hospitals. The quality of vaccine administration practices were graded (1 to 5) and scored (from 20 to 100). Results: Comparison of government (n=8) & private hospitals (n=8) revealed that the cold chain maintenance system was better in the government hospitals. Vaccine administration practices were better in private hospitals. Various incorrect practices in cold chain maintenance and vaccine administration practices were noted in both government and private hospitals. Conclusions: Training in & periodic supervision of cold chain maintenance and vaccine administration practices are essential for achieving the benefits of vaccination.